Program Inovasi “Gerakan Ibu Pintar Atasi Kurang Gizi” (GITAR AKZI) di Desa Panggungrejo Kecamatan Tulungagung - Widi Astuti, Wuri; Andri Mustofa, Linda (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
The prevalence of toddlers in the category of malnutrition status in Indonesia reaches 13% and the death rate caused by malnutrition reaches 54%. There are several factors that cause toddlers to have poor nutritional status, including the mother's nutritional knowledge. The Innovation Program "Smart Mothers' Movement to Overcome Malnutrition" (GITAR AKZI) is a community service activity whose target is for mothers of toddlers to receive education regarding nutrition in children. The aim of this activity is to provide education to mothers of toddlers about fulfilling nutritional requirements for children, inviting mothers to come to the posyandu regularly and teaching mothers about how to prepare healthy snacks for children so that they can improve their children's nutritional status. The method used in this activity is providing education/counseling about nutrition, how to process food and checking the nutritional status of children to 40 target mothers of toddlers, which was carried out at the Posyandu, Stagerejo village, Tulungagung, on 5-8 November 2023. The activity was carried out in 2 ways, namely counseling by assessing the pre and post test results as well as providing a demonstration on how to make vegetable nuggets. The results of this activity showed that there was an increase in knowledge of the target as well as the distribution of vegetable nuggets resulting from the demonstration to mothers of toddlers. Providing education in the form of counseling and demonstrations of processed vegetable nuggets in the "GITAR AKZI" program which has been carried out as an effort to increase the knowledge of mothers of toddlers and improve the nutritional status of children